PENGARUH MANAJEMEN ASET TERHADAP OPTIMALISASI PEMANFAATAN ASET PMI KOTA BANDUNG - Budi Lesmana (LPPM POLITEKNIK LP3I BANDUNG, 2018)
This study aims to analyze the effect of asset management to optimize the use of assets in PMI Kota Bandung. Population is authorized employees and engaged in asset management in PMI Kota Bandung. The sample selection using purposive sampling, with total sample 98 respondents. This study uses primary data, and data collection using structured interviews with the questionnaire. Data analysis using multiple regression analysis. Conclusions of this study are (1) the value of the variable optimization assets, asset inventory, identification asset, legal, audit and asset valuation is very high. Over 50% of respondents gave high ratings on four variables of the study. (2) Variables asset inventory, and legal audit and significant positive effect on alpha 5% asset optimization, and (3) variable asset identification and asset valuation positive effect but not significant at alpha 5% asset optimization.